Perception of cyberbullying in undergraduate students at the National University of Engineering, Lima-Perú, 2020 - Acevedo Rojas, Elba Sissi (2024)
Cyberbullying has been characterized as a form of violence between peers using information and communication technologies (ICT). Before, it was thought that as people matured, bullying cases were left in the past; However, research has shown that the University is no stranger to this problem that is constantly growing, since it has found an effective way to manifest itself, social networks. This cross-sectional and exploratory-descriptive study aims to analyze the prevalence of victims, the frequency of attacks, and the observation of violent behaviors that occur through digital media. The sample was non-probabilistic and was made up of 374 university students. The instrument worked was ad hoc and had internal consistency, a Cronbach's Alpha of 0.903, in addition to its content validity through expert judgment. The results indicated that male students are frequently aggressors and use various modalities for their purpose. On the other hand, women, for the most part, tend to be victims. Of every 100 university students, 14 are aggressors, 29 are victims and 62 bystanders on a recurring basis. This study contains relevant and novel data to identify the magnitude of this problem.